Removal of metformin hydrochloride by Alternanthera philoxeroides biomass derived porous carbon materials treated with hydrogen peroxide. Issue 83 (22nd August 2016) - Huang, Xixian; Liu, Yunguo; Liu, Shaobo; Li, Zhongwu; Tan, Xiaofei; Ding, Yang; Zeng, Guangming; Xu, Yan; Zeng, Wei; Zheng, Bohong
Abstract : Hydrogen peroxide modified biochar (mBC) derived from Alternanthera philoxeroides (AP) biomass was used to investigate the adsorption properties of metformin hydrochloride (MF). Abstract : Hydrogen peroxide modified biochar (mBC) derived from Alternanthera philoxeroides (AP) biomass was used to investigate the adsorption properties of metformin hydrochloride (MF). Additionally, the effects of pH and Cu(ii ) on MF adsorption were also evaluated. Adsorption kinetics and isotherms indicated that the adsorption process of MF on mBC was fitted better to the pseudo-second-order model and Freundlich model, respectively. The adsorption thermodynamic analysis revealed that the adsorption processes of MF were spontaneous and endothermic. In this study, there was a great influence of pH on MF adsorption capacity related to the various species of MF (cationic, zwitterionic and anionic) at different pH. Furthermore, it could be found that the presence of Cu(ii ) facilitated MF adsorption in the range of pH 3.0–7.0, while the adsorption capacity of MF decreased with the increase of Cu(ii ) concentration. At pH < 3 or pH > 7, the presence of Cu(ii ) had only minor effects on MF adsorption.